2021
DOI: 10.1371/journal.pone.0248247
|View full text |Cite
|
Sign up to set email alerts
|

The fat mass and obesity-associated (FTO) gene allele rs9939609 and glucose tolerance, hepatic and total insulin sensitivity, in adults with obesity

Abstract: The objective of the study was to assess associations of the rs9939609 FTO allele to glucose tolerance, hepatic and total insulin sensitivity (IS) in individuals with obesity. From a low-dose hyperinsulinemic euglycemic clamp with glucose-tracer, hepatic IS was assessed by rates of basal and suppressed glucose appearance (Ra), a measure of endogenous glucose production (EGP), and the hepatic insulin resistance index (HIR). Total IS was assessed by rates of glucose infusion (GIR), disappearance (Rd), and metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The polymorphisms of HHEX rs1111875 and rs5015480 are also considered to be associated with insulin secretion and beta‐cell dysfunction 17,25,26 . FTO has been reported to increase the risk of T2DM by affecting insulin sensitivity 27,28 . This study showed that minipigs with diabetes also had diabetes‐related SNPs in these genes or their adjacent intergenic regions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The polymorphisms of HHEX rs1111875 and rs5015480 are also considered to be associated with insulin secretion and beta‐cell dysfunction 17,25,26 . FTO has been reported to increase the risk of T2DM by affecting insulin sensitivity 27,28 . This study showed that minipigs with diabetes also had diabetes‐related SNPs in these genes or their adjacent intergenic regions.…”
Section: Discussionmentioning
confidence: 69%
“…17,25,26 FTO has been reported to increase the risk of T2DM by affecting insulin sensitivity. 27,28 This study showed that minipigs with diabetes also had diabetes-related SNPs in these genes or their adjacent intergenic regions. In addition, loci related to diabetes have also been found in some less-reported genes, such as CCND2, CDKN2B, MRPL34, PXMP4, and GPRIN2, or in their vicinity in human T2DM GWAS studies.…”
Section: Discussionmentioning
confidence: 83%
“…Melina Claussnitzer et al found that the SNP rs1421085 in FTO gene disrupts a conserved motif for the ARID5B repressor, which leads to derepression of a potent preadipocyte enhancer and an increase in lipid storage with the increasing expression of IRX3 and IRX5 (Claussnitzer et al, 2015). Moreover, FTO's related pathways include Glucose/Energy Metabolism and many studies have shown that FTO is closely related to glucose metabolism (Maia-Landim et al, 2018;Yang et al, 2019;Krüger et al, 2020;De Soysa et al, 2021). So, FTO is likely involved in regulating muscle glycogen content.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of obesity and type 2 diabetes in animals will increase significantly with age, due to which aging will lead to a progressive decline in most endocrine functions and meanwhile result in severe metabolic disorder (9). Previous studies have shown that the prevalence of diabetes in the elderly is high, but at present, many studies show significantly lower insulin sensitivity in obese young adults (10). Young people with T2DM or abnormal glucose tolerance have lower βcell sensitivity than healthy old people, which may be related to the great demand for a role of β cells in regulating blood glucose in young people (11).…”
Section: Introductionmentioning
confidence: 99%